Ações judiciais de Plínio, o jovem, no Tribunal dos Centúnviros e na Corte Senatorial (séculos I-II d.C.) - Souza, Dominique Monge Rodrigues de [UNESP] (2013)
The main aim of this paper is to analyze the political career of Pliny the Younger (61/62 AD - 111 AD). Thus we conceived the existence of a relationship between the Senator's cursus honorum and his legal career. Our study begins with the understanding of the Senate's role in the politico-administrative and judicial organization during the governments of the emperors Domitian (81-96 AD), Nerva (96-98 AD) and Trajan (98-117 AD). Such an approach is justified since, even after entering the Senate in 90 AD, this Senator remained active both in the Roman centumviral and senatorial courts. Regarding Pliny’s legal career, we have focused our study on his defenses and objections, before the Roman centumviral and senatorial courts. Based on the interpretation of the processes held on the aforementioned courts, we aim to present a context of power sharing between the Senate and the Emperor. Hence we have made use as documental reference the Pliny’s Epistles, which make reference to his political career as well as his Panegyric speech to Trajan.